2012
DOI: 10.1007/s13197-012-0735-7
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory dynamics of fresh baby corn (Zea mays L.) under modified atmospheres based on enzyme kinetics

Abstract: The respiratory behaviour of baby corn -whole and end-cut, under different temperatures and gas conditions was evaluated to study its respiratory dynamics based upon enzyme kinetics. The dependence of respiration rate on the O 2 and CO 2 concentrations has been described assuming the enzyme kinetics model for combined type of inhibition caused by CO 2 . Various respiratory parameters viz. maximal O 2 consumption rate Michaelis-Menten constants, Inhibition constants under the specified environmental conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
5
11
0
Order By: Relevance
“…The interactive effect of illumination was studied by exposing the plastic containers with each of the atmospheres to light (300 µmol photons m -2 s -1 ) for 48 h, while the controls were maintained in the dark. It has been reported that modified atmospheres delay senescence, extend the life of different crops, and maintain phytochemicals [14]. This is in accordance with our results showing that modified atmospheres resulted in a substantial maintenance of chlorophyll content in the three species under both light and dark conditions (Figs.…”
Section: Storage In Ma Packagingsupporting
confidence: 93%
“…The interactive effect of illumination was studied by exposing the plastic containers with each of the atmospheres to light (300 µmol photons m -2 s -1 ) for 48 h, while the controls were maintained in the dark. It has been reported that modified atmospheres delay senescence, extend the life of different crops, and maintain phytochemicals [14]. This is in accordance with our results showing that modified atmospheres resulted in a substantial maintenance of chlorophyll content in the three species under both light and dark conditions (Figs.…”
Section: Storage In Ma Packagingsupporting
confidence: 93%
“…Cucumbers were packed in bulk inside the large 100 cm × 50 cm LDPE bags of thickness 37.5 μm. For packaging design, the available permeability of film and the desired permeability of the film were calculated (Singh, 2014) 22 . Based on the difference between the available and desired permeability, the number of perforations to be made was decided.Unpackaged cucumbers in plastic crates (inner dimension: 570 × 365 × 143 mm) and packaged cucumbers were kept under three environmental conditions, namely, ambient (25 ± 8°C; 55 ± 14% RH), cool chambers (10°C and 90 ± 5% RH), and evaporative stores (19 ± 3°C; 82 ± 9% RH) to assess the impact of packaging and storage conditions on quality and shelf life of bulk packaged cucumbers.…”
Section: Methodsmentioning
confidence: 99%
“…Respiration rates of fresh cucumber at a temperature of 10.0°C and fixed relative humidity of 85% were investigated using the closed system technique (Kaur et al, 2011) 22,23 . Respiration rate was measured in terms of oxygen consumption rate and carbon dioxide evolution rate.…”
Section: Methodsmentioning
confidence: 99%
“…The PLW was analyzed by measuring the individual package at first and on day of perception (every 3rd day in case of samples stored at 10 °C; 2nd day in case of 30 °C temperature) using an electronic balance (FX 400 FCOSET, India) with a least count of 0.001 g. PLW was expressed as percentage of initial weight of packages (Rai, Gandhi, Kumar, Sharma, & Garg, ; Singh, Kumar, & Kaur, ).…”
Section: Methodsmentioning
confidence: 99%
“…PLW was expressed as percentage of initial weight of packages (Rai, Gandhi, Kumar, Sharma, & Garg, 2012;Singh, Kumar, & Kaur, 2014).…”
Section: Physiological Loss In Weight (Plw)mentioning
confidence: 99%